Common Fixed Point Results for Three Pairs of Self-Maps in Generalized \(E\)-Fuzzy \(b\)-Metric Space - Kumar, Manoj; Manjeet (Communications in Mathematics and Applications, 2025)
In this article, we introduce a new notion of generalized \(E\)-fuzzy \(b\)-metric space and proceed to establish common fixed point theorems for three pairs of self-mappings in this space. These theorems extend and improve specific existing fixed point theorems found in the literature.